THE CURRENT SITUATION AND FUTURE TRENDS OF SOCIAL MEDIA IN MONGOLIA - Oyuntsetseg Densmaa; Gerelchimeg Kaliinaa; Tuul Sembeejav (International Journal of Innovative Technologies in Social Science, 2021)
It might be determined that "Evaluation of Social Media" is the process of world globalization and development of civilization, which is entirely changing principles of the relationship between individual and society, updating into the innovative stage of exploration, procession, and use of information, and completely changing the typical ideas of traditional behavior of people's living and socializing, and creating extraordinary new impacts. Otherwise, the evaluation of media is a vital impact on the development of social relations for civilization. The roles of social rose a year to year and the growth of 2000 - 2021 reached 64 percent (Table1) the scope and impacts of which are increasing a lot. If people can properly use Social Media and obtain good skills on adequate use in the current society, "Social Media" enables a lot of unpredictable active good opportunities of participating in active social life to express own opinions and activity freely despite space and time, expand business activities, improve education, and find like-minded people and combine efforts. The main standard of development of world countries is the relationship between individual and society, the use of Information Technology and Social Media. Without humans, there is no information vs. without information, there is no society. Currently, Social Media tools are the key bridge for social existence, development, and relations.